Ya-Yas in bloom a novel - Wells, Rebecca 1952- (HarperCollins, 2006)
Ya-Yas in bloom reveals the roots of the Ya-Yas' friendship in the 1930s and roars with all the raw power of Vivi Abbott Walker's 1962 T-Bird through sixty years of marriage, child-raising, and hair-raising family secrets.